The baryon cycle of Seven Dwarfs with superbubble feedback - Mina, Mattia; Shen, Sijing; Keller, Benjamin W.; Mayer, Lucio; Madau, Piero; Wadsley, James (Astronomy and astrophysics, 2021)
We present results from a high-resolution, cosmological, ΛCDM simulation of a group of field dwarf galaxies with the “superbubble” model for clustered SN feedback, accounting for thermal conduction and cold gas evaporation. We compared our results to a previous simulation which has the same initial condition and galaxy formation physics (other than SN feedback), but adopts a delayed-cooling model for supernova. The simulated luminous galaxies have blue colors, low star formation efficiencies and metallicities, and high cold gas content, reproducing the observed scaling relations of dwarf galaxies in the Local Volume. Bursty star formation histories and superbubble-driven outflows lead to the formation of kpc-size dark matter (DM) cores when stellar masses reaches M* > 106 M⊙, similar to previous findings. However, the superbubble model appears more effective in destroying DM cusps than the delayed-cooling model in the previous study, reflecting a higher coupling efficiency of SN energy with the ISM. On larger scale, superbubble-driven outflows have a more moderate impact: galaxies have higher gas content, more extended stellar discs, and a smaller metal-enriched region in the circumgalactic medium (CGM). The two halos with Mvir ∼ 109 M⊙, which formed ultra-faint dwarf galaxies with the delayed-cooling mode, remain dark due to the different impact of metal-enriched galactic winds from two nearby luminous galaxies, indicating that the formation of faint dwarfs is highly dependent on feedback and environmental effects. The column density distributions of HI, SiII, CIV and OVI as a function of the scaled impact parameter (b/Rvir) are in good agreement with recent observations of CGM around isolated dwarf galaxies. While HI is ubiquitous with a covering fraction of unity within the CGM, low and intermediate ions like SiII and CIV are less extended (typically confined within 0.2 − 0.3 Rvir), and non-detections are common. OVI is more extended with column density N(OVI) ≳ 1013.5 cm−2 within Rvir, but its mass is only 11% of the total CGM oxygen budget, as the diffuse CGM is highly ionised by the UV background. Superbubble feedback produces CIV and OVI column densities that are an order of magnitude higher than those in the previous study using delayed-cooling feedback. Thus, the CGM and DM cores are most sensitive probes of feedback mechanisms.
Gesehen am 13.12.2021